# Aptitude - Surds and Indices - Discussion

Discussion Forum : Surds and Indices - General Questions (Q.No. 2)
2.
 If a x - 1 = b x - 3 , then the value of x is: b a
 1 2
1
2
 7 2
Explanation:

 Given a x - 1 = b x - 3 b a

 a x - 1 = a -(x - 3) = a (3 - x) b b b

x - 1 = 3 - x

2x = 4

x = 2.

Discussion:
26 comments Page 2 of 3.

Hemz said:   7 years ago
Thanks @Heman.

I can understand very easily. Thank you @Heman.

Priya said:   7 years ago
I am not understanding this method. Please explain me in detail.

Heman said:   7 years ago
(a/b)^x-1=(b/a)x-3.
=>a^x/b^1=a^-3/b^-x,
=>a/b^x-1=a/b^3-x,
=>x-1=3-1,
=>x=2.

I didn't understand for solve the method. Please explain.

AkshI gori said:   8 years ago

Yammu said:   9 years ago
If (b/a) reciprocal how will power gets negative?

Faheem said:   9 years ago
Any one can explain in detail.

Manu said:   10 years ago
The problem can be solved by using the property "If the bases are equal then there powers must be equal". So in order to find the value we have to make the bases equal, after equating solve for x.

SANJIV KUMAR said:   1 decade ago
Everybody can you tell me that how cross multiplication (a)^(2x-4) = (b)^(2x-4) in this answer.